AIRCRAFT MAXIMAL DISTANCE HORIZONTAL FLIGHTS IN THE CONCEPTUAL FRAMEWORK OF SUBJECTIVE ANALYSIS - Goncharenko, Andriy (Proceedings of National Aviation University (archive), 2014)
This paper reflects the aspects of optimal choice for an aircraft’s maximal distance horizontal flights on the basis of multi-alternativeness of the flights operational modes control and at the possibility of the subjectively preferred controls conflicts within the conceptual framework of subjective analysis (preferences theory) in application to the decision making process under the uncertainty